Effect of the pronated pull-up grip width on performance and power-force-velocity profile - Ortega-Rodríguez, R.; Feriche, B.; Almeida, F.; Bonitch-Góngora, J.; Padial, P. (Research Quarterly for Exercise and Sport, 2021)
Purpose: The objective of this study was to investigate the influence of the grip width on the power-force-velocity-profile, the maximal strength, and performance during a repetition to failure test in the pull-up exercise (PU).